Divorce Due to Family Economic Problems (Case Study at the Belopa Religious Court in 2022-2023) - Nafila, Selvi; Muchtar, M Ilham; Rapung, Rapung (Journal of Family Law and Islamic Court, 2024)
This thesis is motivated by the breakdown of a marriage between husband and wife due to disharmony in the household. By formulating the problem of how the divorce rate is due to family economic problems and analyzing divorce due to family economic problems in the Belopa Religious Court, the author conducted research with the aim of finding out the level and analyzing the factors that trigger divorce due to family economic problems in the Belopa Religious Court. The author uses a qualitative method, with the data sources used being primary and secondary. Then data collection techniques use interview, observation, documentation and data information collection methods. The data analysis techniques used are data reduction, data presentation and conclusions. The results of this research show that the divorce rate due to family economic problems in the Belopa Religious Court is quite significant, with the number of cases submitted in 2022 being 4 cases and in 2023 being 3 cases. case. Apart from economic factors, there are other internal and external factors that cause divorce, such as the husband's lack of responsibility, lack of transparency in economic matters and interference by third parties. Divorce cases due to family economic problems are also influenced by other factors such as infidelity, domestic violence and other family conflicts.